2022
DOI: 10.1177/20551169221074961
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine-based near-infrared lymphography for real-time detection of lymphatics in a cat with multiple mast cell tumours

Abstract: Case summary An 11-year-old female domestic shorthair cat was presented with cutaneous mast cell tumours (MCTs) localised at the right temporal region, the left buccal region and on the third digit of the right thoracic limb. Staging was negative and locoregional lymph nodes appeared normal, based on clinical findings. During surgery, real-time indocyanine green (ICG)-based lymphography was performed to detect the cutaneous draining pattern of all the primary MCTs. ICG was injected intracutaneously in four qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…contrast-enhanced ultrasound (CEUS) [32], single-photon emission computed tomography (SPECT) [33], positron emission tomography (PET) [34], pre-and intraoperative lymphoscintigraphy, and the injection of blue dyes for direct visualization or fluorescent dyes for near-infrared (NIR) fluorescent imaging [35]. Corresponding evaluations of indirect radiographic [36][37][38] and CT lymphography [39][40][41][42], lymphoscintigraphy [15,20,24,[43][44][45][46][47], CEUS [25,48], methylene blue staining [20,24,47], and NIR-lymphography [14,47,[49][50][51] are also available for dogs and, most recently, also for cats [26,52].…”
Section: Sln Mapping In Companion Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…contrast-enhanced ultrasound (CEUS) [32], single-photon emission computed tomography (SPECT) [33], positron emission tomography (PET) [34], pre-and intraoperative lymphoscintigraphy, and the injection of blue dyes for direct visualization or fluorescent dyes for near-infrared (NIR) fluorescent imaging [35]. Corresponding evaluations of indirect radiographic [36][37][38] and CT lymphography [39][40][41][42], lymphoscintigraphy [15,20,24,[43][44][45][46][47], CEUS [25,48], methylene blue staining [20,24,47], and NIR-lymphography [14,47,[49][50][51] are also available for dogs and, most recently, also for cats [26,52].…”
Section: Sln Mapping In Companion Animalsmentioning
confidence: 99%
“…Lately, several metareviews in human medicine have confirmed NIR imaging using ICG as a reliable mapping technique compared with the gold standard lymphoscintigraphy [35,77]. After NIR SLN mapping in dogs was initially described in experimental studies in dogs and pigs [50], it is now gaining increased interest in veterinary surgical oncology [14,49,52]. Beer et al published a retrospective study on NIR lymphography in dogs with mast cell tumors.…”
Section: Near-infrared Lymphographymentioning
confidence: 99%
See 2 more Smart Citations
“…A tendency to lymphatic spread and nodal metastases is reported for various feline solid tumors [ 11 , 28 , 29 ]. In a recent study, metastases to the lymph nodes have been documented in 58.8% of cats with MCT, underscoring the importance of nodal assessment also in this species [ 30 ]. However, there is still considerable inconsistency among studies on indications and methods for nodal staging in cats, and most studies do not even include information on the status of the lymphatic basin [ 11 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%